Low Healthy Eating Index-2015 Is Associated With Sarcopenia Among US Adult Population. (7th June 2021) - Bigman, Galya; Ryan, Alice
Abstract: Objectives: The Healthy Eating Index-2015 (HEI-2015), which is designed to reflect the 2015–2020 Dietary Guidelines for Americans (DGA), and its association with muscle function decline (i.e., sarcopenia) is less known in the U.S. Our study aim was to examine the associations between HEI-2015 component and total scores with sarcopenia in a nationally representative sample of the U.S. adult population. Methods: This cross-sectional study used data from the National Health and Nutrition Examination Surveys of 2011–2014. Sarcopenia was assessed by handgrip strength measure using an average score of six trails (<35.5kg for males, <20.0kg for females). HEI-2015 was computed from data of two 24-hour dietary recalls and comprised 13 components (e.g., vegetables, greens and beans, fruits, dairy, protein foods, whole grains, fatty acid ratio, refined grains, sodium, saturated fats, and added sugars). Each component was scored on density out of 1000 calories and summed to a total score divided into quintiles. Weighted logistic regressions examined the study aim while controlling for associated covariates: age, sex, race/ethnicity, education, body mass index (BMI), physical activity, comorbidity, medication use, smoking status, and alcohol use. Results: The sample included 9006 eligible participants aged 20–80 years, of those, 14.4% had sarcopenia, where males had higher sarcopenia prevalence than females (18.4 vs. 10.7%, P  < 0.001), and participants with sarcopenia were older (p < 0.001). Scores for HEI-2015 were total: 54.2 ± 13.6 (mean ± SD), and in the lowest and highest quintiles: 35.9 ± 4.8 and 73.9 ± 5.95, respectively. In the multivariable model, participants in the highest HEI-2015 quintile had 28% lower odds of having sarcopenia (Odds Ratio(OR) = 0.72, 95%CI: 0.55–0.94) compared with those in the lowest quintile. Among the HEI-2015 components; consuming adequate amount of protein foods, greens and beans, vegetables, and whole fruits reduced the odd of having sarcopenia by 18–23%. Conclusions: The findings suggest that higher compliance to the 2015–2020 DGA might reduce sarcopenia among U.S. adults, particularly adequate intakes of protein foods, greens and beans, vegetables, and whole fruits. Funding Sources: Department of Veterans Affairs (VA) Advanced Special Fellowship in Geriatrics, Baltimore Geriatric Research, Education and Clinical Center.